Extracellular Vesicles in Prostate Cancer Carcinogenesis, Diagnosis, and Management - Vlaeminck-Guillem, Virginie (Frontiers in Oncology, 2018)
Extracellular vesicles (EVs), especially exosomes, are now well recognized as major ways by which cancer cells interact with each other and stromal cells. The meaningful messages transmitted by the EVs are carried by all components of the EVs, i.e. the membrane lipids and the cargo (DNAs, RNAs, microRNAs, long non coding RNAs, proteins). They are clearly part of the armed arsenal by which cancer cells obtain and share more and more advantages to grow and conquer new spaces. Identification of these messages offers a significant opportunity to better understand how a cancer occurs and then develops both locally and distantly. But it also provides a powerful means by which cancer progression can be detected and monitored. In the last few years, significant research efforts have been made to precisely identify how the EV trafficking is modified in cancer cells as compared to normal cells and how this trafficking is altered during cancer progression. Prostate cancer has not escaped this trend. The aim of this review is to describe the results obtained when assessing the meaningful content of prostate cancer- and stromal-derived EVs in terms of a better comprehension of the cellular and molecular mechanisms underlying prostate cancer occurrence and development. This review also deals with the use of EVs as powerful tools to diagnose non-indolent prostate cancer as early as possible, and to accurately define, in a personalized approach, its present and potential aggressiveness, its response to treatment (androgen deprivation, chemotherapy, radiation, surgery), and the overall patients’ prognosis. Prostate cancer has not escaped this trend. The aim of this review is to describe the results obtained when assessing the meaningful content of prostate cancer- and stromal-derived EVs in terms of a better comprehension of the cellular and molecular mechanisms underlying prostate cancer occurrence and development. This review also deals with the use of EVs as powerful tools to diagnose prostate cancer as early as possible, and to accurately define, in a personalized approach, its present and potential aggressiveness, its response to treatment (androgen deprivation, chemotherapy), and the overall patients’ prognosis.